Description of new species of Mycobacterium terrae complex isolated from sewage at the São Paulo zoological park foundation in Brazil - Romagnoli, Camila Lopes; Conceição, Emilyn Costa; Machado, Edson; Barreto, Leonardo Bruno Paz Ferreira; Sharma, Abhinav; Silva, Natalia Maria; Marques, Lucas Evangelista; Juliano, Maria Aparecida; da Silva Lourenço, Maria Cristina; Digiampietri, Luciano Antonio; Suffys, Philip Noel; Leão, Sylvia Cardoso; et al. (Frontiers in Microbiology, 2024)
Five mycobacterial isolates from sewage were classified as members of the genus Mycobacterium but presented inconclusive species assignments. Thus, the isolates (MYC017, MYC098, MYC101, MYC123 and MYC340) were analysed by phenotypical, biochemical, matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF-MS) and genomic features to clarify their taxonomic position. Phenotypic analysis and biochemical tests did not distinguish these isolates from other non-pigmented mycobacteria. In contrast, MALDI-TOF MS analysis showed that isolates were not related to any previously described Mycobacterium species. Comparative genomic analysis showed values of ANI and dDDH between 81.59-85.56% and 24.4-28.8%, respectively, when compared to the genomes of species of this genus. In addition, two (MYC101 and MYC123) presented indistinguishable protein spectra from each other and values of ANI = 98.57% and dDDH = 97.3%, therefore being considered as belonging to the same species. Phylogenetic analysis grouped the five isolates within the Mycobacterium terrae complex (MTC) but in a specific subclade and separated from the species already described and supported by 100% bootstrap value, confirming that they are part of this complex but different from earlier described species. According to these data, we propose the description of four new species belonging to the Mycobacterium genus: (i) Mycobacterium defluvii sp. nov. strain MYC017 T (=ATCC TSD-296 T =JCM 35364 T ), (ii) Mycobacterium crassicus sp. nov. strain MYC098 T (=ATCC TSD-297 T =JCM 35365T), (iii) Mycobacterium zoologicum sp. nov. strain MYC101 T (=ATCC TSD-298 T =JCM 35366 T ) and MYC123 (=ATCC BAA-3216 =JCM 35367); and (iv) Mycobacterium nativiensis sp. nov. strain MYC340 T (=ATCC TSD-299 T =JCM 35368 T ).